Amount and composition of total fatty acids in red and yellow bone marrow are altered with changes in bone mineral density - Sabrina Ehnert; Anna J. Schreiner; Claudine Seeliger; Josef Ecker; Fabian Springer; Gerhard Liebisch; Philipp Hemmann; Tina Histing; Andreas K. Nussler (EXCLI Journal : Experimental and Clinical Sciences, 2023)
There is general consent that with decreasing bone mineral density the amount of marrow adipose tissue increases. While image-based techniques, claim an increase in saturated fatty acids responsible for this effect, this study shows an increase in both saturated and unsaturated fatty acids in the bone marrow. Using fatty acid methyl ester gas chromatography-mass spectrometry, characteristic fatty acid patterns for patients with normal BMD (N = 9), osteopenia (N = 12), and osteoporosis (N = 9) have been identified, which differ between plasma, red bone marrow and yellow bone marrow. Selected fatty acids, e.g. FA10:0, FA14:1, or FA16:1 n-7 in the bone marrow or FA18:0, FA18:1 n-9, FA18:1 n-7, FA20:0, FA20:1 n-9, or FA20:3 n-6 in the plasma, correlated with osteoclast activity, suggesting a possible mechanism how these fatty acids may interfere with BMD. Although several fatty acids correlated well with the osteoclast activity and BMD, there was not a single fatty acid contained in our fatty acid profile that can be claimed for controlling BMD, a fact that may be attributed to the genetic heterogeneity of the patients.